Calcium sulfate whisker one-step preparation using semi-dry flue gas desulfurization ash and directional growth control. (25th March 2021) - Zhou, Di; Wei, Rufei; Zhu, Yulong; Long, Hongming; Huang, Bangfu; Wang, Yifan; Wu, Shoucang
Abstract: Calcium sulfate whiskers were prepared under hydrothermal conditions by a one-step method using semi-dry flue gas desulfurization ash with iron ore sintering as the raw material. The effects of temperature, time, speed, and other factors on the calcium sulfate whiskers morphology and growth rule were systematically studied in a high-pressure hydrothermal reaction system. The results demonstrate that the presence of calcium carbonate inhibits high-efficiency desulfurization ash oxidation at low temperatures and affects calcium sulfate whiskers growth. The calcium sulfite content in flue gas desulfurization ash increased to 81.17% when glacial acetic acid was used as the raw material for pickling. In the supersaturated hydrothermal system, the one-step preparation of calcium sulfate whiskers from flue gas desulfurization ash was successful at a reaction temperature of 140 °C, time of 30 min, initial pressure of 2 MPa, initial solid–liquid ratio of 1:30, and rotation speed of 300 r/min. A medium solution purification link was added to create calcium sulfate whiskers products in the hydrothermal reaction system. Calcium sulfate whiskers products with an average diameter of less than 0.8 μm and average aspect ratio of over 140 were obtained at a purification temperature of 60 °C, purification agent concentration of 0.6 mmol/g, temperature of 140 °C, time of 30 min, and speed of 100 r/min.